Cytoarchitectonic features of the neocortex, archicortex and amygdala of white rats after a 20-minute occlusion of the common carotid arteries - V. A. Akulinin; D. B. Avdeev; A. S. Stepanov; A. V. Gorbunova; S. S. Stepanov; I. G. Tsuskman (Бюллетень сибирской медицины, 2020)
Purpose. The study is focused on glioarchitectonics of the neocortex, archicortex and amygdala of Wistar white rats in normal state and after a 20-minute occlusion of the common carotid arteries.Materials and methods. Light (stained with hematoxylin and eosin) microscopy, immunohistochemistry (GFAP), and morphometry were used to study the distribution, shape, and area of GFAP-immunopositive brain cells in the normal range (n = 5) and at days 1, 3, 7, 14, 30 (n = 25) after acute ischemia.Results. Focal changes were found in the density of the glial network: decrease and increase in the local content of GFAP-positive material. Reactive, dystrophic and necrobiotic changes in neurons after acute ischemia were accompanied by reorganization of neuroglia and increase in the neuroglia index in certain zones by 1.2–1.5 times. The surface area of the particles in GFAP-positive astrocytes in sections of the neocortex in the control was 8.4–18.1, but after 3 days after ischemia this rate in some parts of the neocortex rose to 45.0–59.3%. In the hippocampus this rate was 8.1% and 16.2%, and in the amygdala it was 12.6% and 21.2%. Hypertrophy of mature astrocytes was manifested by the increase in the diameter, degree of branching and length of their processes.Conclusion. The obtained data are considered as a phenomenon of ischemic preconditioning and activation of protective processes in neuro-glio-vascular microcomplexes.